PENGARUH BRAND AWARENESS, BRAND AMBASSADOR DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE DI KOTA DENPASAR - I Gede Dika Wiguna; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (EMAS, 2023)
Abstract This study aims to explain the influence of brand awareness, brand ambassadors and electronic word of mouth on purchasing decisions at e-commerce Shopee in Denpasar City. The population in this study are people who have the Shopee application in Denpasar City. Sampling using a non-probability sampling method, namely a number of 100 respondents. The analysis technique used is multiple linear regression analysis. The results showed that brand awareness had a positive and significant effect on purchasing decisions, brand ambassadors had a positive and significant effect on purchasing decisions and electronic word of mouth had a positive and significant effect on purchasing decisions. Suggestions for further researchers can develop this research by adding other variables.